The Effect of Tax Fairness Dimension on Government Regulation No. 55 of 2022 To SMEs Tax Payers’ Compliance - Indra Amanda Setya Putri; Aisyaturrahmi (International Environmental Conferrence on Biosustainability Advancement, 2024)
Incentive is given to SMEs tax payers to keep their business alive due adverse effect of pandemic. Then government publish government regulation number 55 of 2022 to keep the incentive with fairness as the main principle. But Gerbing (1988) revealed that tax fairness is a multidimensional, so that this study aims to examine the impact of tax justice dimensions on government regulation number 55 of 2022 (PP No.55/2022) towards SMEs tax payers’ compliance. This research used quantitative method with questionnaire as data collection method. Moreover, respondents in this research were SMEs in Surabaya who has tax ID number and turnover per year more than 300M. the data analysis technique used was SEM-PLS with Smart PLS software. The result showed that there was positive effect of general fairness, exchange with government, special provisions, and tax rate on SMEs tax payers’ compliance. Besides that, self-interest has no effect on SMEs tax payers’ compliance.